Analysis Of Factors Influencing Timeliness In Submission Of Company Financial Reports In Manufacturing Companies In The Consumer Goods Industry Sector On The Indonesia Stock Exchange - Sparta; Wanda Cantikaputri Indriana (Jurnal Ekonomi, Manajemen dan Perbankan (Journal of Economics, Management and Banking), 2025)
The purpose of this research is to test and analys the effect of leverage (DER), liquidity (Current Ratio), company age, and company size on the timeliness of financial reporting among manufacturing companies in the consumer goods sector, specifically in the food and beverage subsector, listed on the Indonesia Stock Exchange (IDX) from 2019 to 2023. A total of 150 sample data were obtained from secondary sources in the form of annual financial reports of food and beverage sector companies listed on the IDX for the period 2019-2023. The testing method in this research used logistic regression analysis, supported by the SPSS software version 30.0. Based on the logistic regression analysis, the results show that leverage and liquidity variables have a significant negative impact on the timeliness of financial reporting, while company age and company size variables do not affect the timeliness of financial reporting.